PENGEMBANGAN APLIKASI PEMBELAJARAN INOVATIF DALAM PEMBELAJARAN BAHASA ARAB BERBASIS WEB - Rambe, Pangadilan (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
The purpose of this study was to create a web-based application that has been developed from the introduction of animal names, fruit names and school equipment in Arabic, to find out how to validate web-based applications that have been developed in Arabic, to find out the level of application of web applications in Arabic, and to find out the effectiveness level of innovative learning applications in web-based programming languages. The population in this study was MIN 1 teachers from Pekanbaru who were dangerous with 2 people. The sample technique used was purposive sampling which is based on the criteria set by the researcher. The data collection technique used was documentation, questionnaires and interviews. For data analysis, descriptive statistics was used. Based on the results of data analysis, it can be concluded that the practicality of the application was 84.83% which indicates practical applications for MIN 1 Pekanbaru city.